Decision Support System for Determining Homeroom Teachers at SMPN 3 Porsea Using the Simple Additive Weighting Method - Amran Sitohang; Petti Indrayati Sijabat (Marqcha Institute, 2023)
Determination of homeroom teachers at SMPN 3 Porsea using the Simple Additive Weighting method. The model used in this decision support system is Fuzzy Multiple Attribute Decision Making (FMADM) which is a system that can produce an alternative decision that can be used as a tool in making decisions. Based on government demands in the field of education to improve the quality of homeroom teachers, system development This decision support is one way to assist in determining the appropriate teacher to be a homeroom teacher. The SAW method was chosen because this method determines the weight value for each attribute, then proceed with a ranking process that will select the best alternative from a number of alternatives in question, namely the teacher who has the highest score based on each predetermined criterion. With this ranking method, the assessment will be more precise because it is based on the criteria and weights that have been determined so as to get accurate results as a decision aid to determine the homeroom teacher at SMPN 3 Porsea.